Monte Carlo study of the effects of system geometry and antiscatter grids on cone‐beam CT scatter distributions. Issue 5 (25th April 2013) - Sisniega, A.; Zbijewski, W.; Badal, A.; Kyprianou, I. S.; Stayman, J. W.; Vaquero, J. J.; Siewerdsen, J. H.
Abstract : Purpose: : The proliferation of cone‐beam CT (CBCT) has created interest in performance optimization, with x‐ray scatter identified among the main limitations to image quality. CBCT often contends with elevated scatter, but the wide variety of imaging geometry in different CBCT configurations suggests that not all configurations are affected to the same extent. Graphics processing unit (GPU) accelerated Monte Carlo (MC) simulations are employed over a range of imaging geometries to elucidate the factors governing scatter characteristics, efficacy of antiscatter grids, guide system design, and augment development of scatter correction. Methods: : A MC x‐ray simulator implemented on GPU was accelerated by inclusion of variance reduction techniques (interaction splitting, forced scattering, and forced detection) and extended to include x‐ray spectra and analytical models of antiscatter grids and flat‐panel detectors. The simulator was applied to small animal (SA), musculoskeletal (MSK) extremity, otolaryngology (Head), breast, interventional C‐arm, and on‐board (kilovoltage) linear accelerator (Linac) imaging, with an axis‐to‐detector distance (ADD) of 5, 12, 22, 32, 60, and 50 cm, respectively. Each configuration was modeled with and without an antiscatter grid and with (i) an elliptical cylinder varying 70–280 mm in major axis; and (ii) digital murine and anthropomorphic models. The effects of scatter were evaluated in terms of the angular distribution of scatter incident upon the detector, scatter‐to‐primary ratio (SPR), artifact magnitude, contrast, contrast‐to‐noise ratio (CNR), and visual assessment. Results: : Variance reduction yielded improvements in MC simulation efficiency ranging from ∼17‐fold (for SA CBCT) to ∼35‐fold (for Head and C‐arm), with the most significant acceleration due to interaction splitting (∼6 to ∼10‐fold increase in efficiency). The benefit of a more extended geometry was evident by virtue of a larger air gap—e.g., for a 16 cm diameter object, the SPR reduced from 1.5 for ADD = 12 cm (MSK geometry) to 1.1 for ADD = 22 cm (Head) and to 0.5 for ADD = 60 cm (C‐arm). Grid efficiency was higher for configurations with shorter air gap due to a broader angular distribution of scattered photons—e.g., scatter rejection factor ∼0.8 for MSK geometry versus ∼0.65 for C‐arm. Grids reduced cupping for all configurations but had limited improvement on scatter‐induced streaks and resulted in a loss of CNR for the SA, Breast, and C‐arm. Relative contribution of forward‐directed scatter increased with a grid (e.g., Rayleigh scatter fraction increasing from ∼0.15 without a grid to ∼0.25 with a grid for the MSK configuration), resulting in scatter distributions with greater spatial variation (the form of which depended on grid orientation). Conclusions: : A fast MC simulator combining GPU acceleration with variance reduction provided a systematic examination of a range of CBCT configurations in relation to scatter, highlighting the magnitude and spatial uniformity of individual scatter components, illustrating tradeoffs in CNR and artifacts and identifying the system geometries for which grids are more beneficial (e.g., MSK) from those in which an extended geometry is the better defense (e.g., C‐arm head imaging). Compact geometries with an antiscatter grid challenge assumptions of slowly varying scatter distributions due to increased contribution of Rayleigh scatter.